Exome Sequencing Reveals De Novo Variants in Congenital Scoliosis - Murakami, Kohei; Kikugawa, Shingo; Seki, Shoji; Terai, Hidetomi; Suzuki, Takako; Nakano, Masaki; Takahashi, Jun; Nakamura, Yukio (Journal of Pediatric Genetics, 2021)
Congenital scoliosis (CS) is a lateral curvature of the spine characterized by the presence of vertebral anomalies. Pathogenic genetic variants in the TBX6 gene are one of the causes of CS. However, since many clinically diagnosed cases of CS are without known TBX6 gene variations, this study aims to uncover new genes related to disease susceptibility of CS by exome sequencing (ES). This study employed ES in a cohort of 5 Japanese patients with CS and their healthy parents or a sister for a total of 16 samples among 5 families. Variant interpretation was performed using SIFT, PolyPhen-2, Mutation Taster, and CADD. Four de novo variants were identified by ES and confirmed by Sanger sequencing: 1 frameshift variant (SHISA3) and 3 missense variants (AGBL5, HDAC4, and PDE2A). ES also uncovered 1 homozygous variant in the MOCOS gene. All of these variants were predicted to be deleterious by SIFT, PolyPhen-2, Mutation Taster, and/or CADD. The number of de novo variants identified in this study was exactly what would be expected by chance. Additional functional studies or gathering matched patients using Gene Matcher are needed.
Keywords: congenital scoliosis; exome sequencing; de novo variants